Improving Chronic Diseases Management Through the Development of an Evidence‐Based Resource. Issue 3 (28th March 2015) - Khalil, Hanan; Chambers, Helen; Munn, Zachary; Porritt, Kylie
ABSTRACT Objective There is a large gap between evidence and practice within health care, particularly within the field of chronic disease. To reduce this gap and improve the management of chronic disease, a collaborative partnership between two schools within a large university and two industry partners (a large regional rural hospital and a rural community health center) in rural Victoria, Australia, was developed. The aim of the collaboration was to promote the development of translation science and the implementation of evidence‐based health care in chronic disease with a specific focus on developing evidence‐based resources that are easily accessed by clinicians. Methods A working group consisting of members of the collaborating organizations and an internationally renowned expert reference group was formed. The group acted as a steering committee and was tasked with developing a taxonomy of the resources. In addition, a peer review process of all resources was established. A corresponding reference group consisting of researchers and clinicians who are clinical experts in various fields was involved in the review process. The resources developed by the group include evidence summaries and recommended practices made available on a web‐based database, which can be accessed via subscription by clinicians and researchers worldwide. Results As of mid‐2014, there were 109 new evidence summaries and 25 recommended practices detailing the best available evidence on topics related to chronic disease management including asthma, diabetes, heart failure, dementia, and others. Training sessions and a newsletter were developed for clinicians within the node to enable them to use the content effectively. Linking Evidence to Action This paper describes the processes involved in the successful development of the collaborative partnership and its evolution into producing a valuable resource for the translation of evidence into practice in the areas of chronic disease management. The resource developed is being used by clinicians to inform practice and support their clinical decision making.